Urchin-like NiO Superstructures Prepared by Simple Thermal Decomposition Process - Jiao, Hua (Nano-Micro Letters, 2011)
Urchin-like NiO superstructures have been prepared via a thermal decomposition reaction of NiC2O4 at 400°C for 1 h. The morphology and structure of the synthesized urchin-like superstructures have been characterized by X-ray diffraction, field emission scanning electron microscopy and transmission electron microscopy. The results show that urchin-like NiO superstructures were a polycrystal with cubic structure and typical diameters of 200 to 500 nm and the self-assembly nanoparticles average diameter is 14 nm. The as-prepared NiO superstructures have a high Brunauer-Emmett-Teller surface area of about 60.32 m2/g. The UV-vis spectrum of urchin-like NiO consists of one peak at 357 nm (3.47 eV).